META ANALISIS: PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA INTERAKTIF BERBASIS ADOBE FLASH PADA JENJANG SMP - Nurlaela Saadah; Indra Budiman (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
This research is motivated by the low use of media in learning mathematics, because students’ feel bored and difficult to understand mathematics learning. Therefore, there is a need for innovation, namely with Adobe Flash-based interactive mathematics learning media. The purpose of this research is to determine the effectiveness and impact of interactive learning media assisted by Adobe Flash at the junior high school level. This research uses a meta-analysis research design, where meta-analysis is a study of previous journals with the same problem. So that they can find out the results and conclusions. The data collection technique used in the research is written documentation of Adobe Flash-based learning media at the junior high school level. The author uses 19 articles for reference. The articles are sourced from the Google Scholar and Sinta websites. The results of the research show that Adobe Flash-based interactive mathematics learning media has a positive impact so that it is more practical and effective to use in the mathematics learning process.